2017
DOI: 10.1155/2017/8270498
|View full text |Cite
|
Sign up to set email alerts
|

Progenitor Cells for Arterial Repair: Incremental Advancements towards Therapeutic Reality

Abstract: Coronary revascularization remains the standard treatment for obstructive coronary artery disease and can be accomplished by either percutaneous coronary intervention (PCI) or coronary artery bypass graft surgery. Considerable advances have rendered PCI the most common form of revascularization and improved clinical outcomes. However, numerous challenges to modern PCI remain, namely, in-stent restenosis and stent thrombosis, underscoring the importance of understanding the vessel wall response to injury to ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 145 publications
(144 reference statements)
0
28
0
Order By: Relevance
“…In the setting of DVT, endothelial progenitor cells (EPCs), which are a type of bone marrow‐derived circulating progenitor cell in the endothelial lineage, have been reported to have the abilities to home in on and migrate to disease sites to facilitate thrombus recanalization and resolution by neovascularization, increase new blood vessel formation at the injured site, and secrete a variety of vasoactive and angiogenic factors to improve angiogenesis . Furthermore, EPCs have the capacity to protect differentiated endothelial cells from apoptosis, thereby preserving their angiogenic potential under conditions of oxidative stress . In our previous study, we demonstrated that the transplantation of normal and gene‐modified bone marrow‐derived EPCs altered the vein microenvironment and facilitated thrombus resolution in a rat model of vein thrombosis .…”
Section: Introductionmentioning
confidence: 99%
“…In the setting of DVT, endothelial progenitor cells (EPCs), which are a type of bone marrow‐derived circulating progenitor cell in the endothelial lineage, have been reported to have the abilities to home in on and migrate to disease sites to facilitate thrombus recanalization and resolution by neovascularization, increase new blood vessel formation at the injured site, and secrete a variety of vasoactive and angiogenic factors to improve angiogenesis . Furthermore, EPCs have the capacity to protect differentiated endothelial cells from apoptosis, thereby preserving their angiogenic potential under conditions of oxidative stress . In our previous study, we demonstrated that the transplantation of normal and gene‐modified bone marrow‐derived EPCs altered the vein microenvironment and facilitated thrombus resolution in a rat model of vein thrombosis .…”
Section: Introductionmentioning
confidence: 99%
“…The levels of EPCs, which contributed to endothelial reparation via paracrine effect or transdifferentiating into mature endothelial cells [8], reduced signi cantly in patients with DM and other diabetes-related disorders. Transplantation of exogenous EPCs was considered as a potential method to promote endothelial reparation via elevating the circulating EPC level directly in a rabbit model [34].…”
Section: Discussionmentioning
confidence: 99%
“…However, unfavorable events after stent implantation, such as in-stent restenosis and late stent thrombosis, remain a serious clinical challenge [3,4]. A large body of evidence showed that endothelium injury caused by DM or interventional therapy contributed to these unfavorable vascular events [5][6][7][8]. Previous studies demonstrated that endothelial progenitor cells (EPCs) were vital in endothelial reparation [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Simard et al . ), to our knowledge there is no study showing incorporation of EPCs into the pre‐existing vasculature of healthy animals as a means of endothelial repair in response to an acute bout of exercise. Assuming an increase in EPCs always reflects endothelial damage is, therefore, a flawed assumption that should be questioned considering that the currently available data on healthy individuals do not support an increase in CECs due to exercise.…”
mentioning
confidence: 92%